Accounting for Growth with New Inputs: Theory and Evidence - Feenstra, Robert C.; Markusen, James R.; Zeile, William J. (American Economic Review, 2016)
Since the work of Robert M. Solow (1957), it has been known that technological change accounts for a significant portion of GNP growth in industrialized economies. This technological change has been measured either by the estimated time trend in regressions of aggregate output on inputs or by indexes of total factor productivity. Since under either method productivity is measured as a residual, it incorporates all factors that influence GNP growth other than the increase in measured inputs. Despite various refinements to the measurement of total factor productivity, there still is no convincing explanation for its source (see Dale W. Jorgenson and Zvi Griliches, 1967; Solow, 1988). Recent literature has suggested a potential source of productivity gains: the creation of new inputs under monopolistic competition. Wilfred Ethier (1982) has argued that the development of new intermediate inputs leads to greater specialization in the use of resources and to higher productivity (see also Markusen, 1989). Subsequent authors, including Paul M. Romer (1990) and Gene Grossman and Elhanan Helpman (1991), have examined models in which continuous growth is made possible by the creation of new inputs. Romer (1987) has considered the form of the aggregate production function in such an economy and has argued that conventional growth accounting, assuming constant returns to scale, may be incorrect. In this paper we shall examine how to account for growth when new inputs are being created. In particular, we are interested in obtaining a decomposition of growth into that due to a higher quantity of existing inputs, and that due to a greater range of inputs. In Section I, we show how this decomposition can be obtained for a constantelasticity-of-substitution (CES) production function, obtaining an exact quantity index in the presence of new inputs. In Section II we examine the CES cost function, and show how an implicit quantity index is constructed. In Section III we consider an empirical application to the productivity growth of industries within the major business groups (chaebol) of South Korea. We find that productivity is significantly correlated with the entry of new input-producing firms into the chaebol, as expected from our theoretical results.